2017
DOI: 10.1055/s-0037-1606579
|View full text |Cite
|
Sign up to set email alerts
|

A Multipronged Intervention for Treatment of Psychotic Symptoms from Post-football Traumatic Brain Injury in an Adolescent Male: A Case Report

Abstract: Traumatic brain injury (TBI) is common among childrenaggression and disinhibition) are the most common psychological changes following a TBI in children and adolescents. 7,8Depression and anxiety can also develop following TBI. 9 In some individuals, such symptoms resolve within weeks, while in others, these symptoms remain for years, and a history of multiple TBIs increases risk for developing chronic depression and cognitive impairments later in life. 10Hallucinations are a less common form of psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“… Notes a Two research articles [ 67 , 100 ] reported two studies of different study designs and as such, data reported on study design are for 61 studies b All case studies c Excludes case studies; two before-after without control group, three controlled interventions d All conducted in the United States e Sixteen studies [ 49 51 , 53 , 62 , 67 , 68 , 74 , 76 , 83 , 89 , 90 , 92 , 99 , 103 , 104 ] examined integrated care for individuals with TBI and more than one type of MHSU f Some studies include more than one type of treatment and as such, the number of articles reported across treatment types exceeds 49 studies ED: Emergency department; MHSU: Mental health disorders or substance use; OT: Occupational therapy; PTSD: Post-traumatic stress disorder; rTMS: Repetitive transcranial magnetic stimulation; TBI: Traumatic brain injury …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Notes a Two research articles [ 67 , 100 ] reported two studies of different study designs and as such, data reported on study design are for 61 studies b All case studies c Excludes case studies; two before-after without control group, three controlled interventions d All conducted in the United States e Sixteen studies [ 49 51 , 53 , 62 , 67 , 68 , 74 , 76 , 83 , 89 , 90 , 92 , 99 , 103 , 104 ] examined integrated care for individuals with TBI and more than one type of MHSU f Some studies include more than one type of treatment and as such, the number of articles reported across treatment types exceeds 49 studies ED: Emergency department; MHSU: Mental health disorders or substance use; OT: Occupational therapy; PTSD: Post-traumatic stress disorder; rTMS: Repetitive transcranial magnetic stimulation; TBI: Traumatic brain injury …”
Section: Resultsmentioning
confidence: 99%
“… e Sixteen studies [ 49 51 , 53 , 62 , 67 , 68 , 74 , 76 , 83 , 89 , 90 , 92 , 99 , 103 , 104 ] examined integrated care for individuals with TBI and more than one type of MHSU …”
Section: Resultsmentioning
confidence: 99%
“…Commonly identified psychological interventions used with individuals with childhood onset ABI and CP were acceptance and commitment therapy (ACT) ( 34 , 37 , 38 , 40 ), psychotherapy ( 39 , 41 ), and CBT ( 33 , 35 , 36 , 42 , 43 ), in combination with components of family therapy ( 34 ), psychoeducation ( 33 , 36 , 43 ), and Stepping Stones Triple P (SSTP) ( 40 ). Studies reporting on ACT were limited to individuals with childhood onset ABI, while studies investigating the use of psychotherapy only included individuals with CP.…”
Section: Resultsmentioning
confidence: 99%
“…Mindfulness and cognitive defusion were key techniques used. Interventions involved group therapy sessions ( 37 , 38 , 40 ), with one study involving individual sessions ( 34 ). Groups ranged from two to six people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation